Variability in Some Irrigation Related Soil Properties of the Alluvial Soils Formed by the Yesilirmak River - SIMSEK, HUSEYIN; OZTEKIN, TEKIN; DURAK, ALPER (Asian Journal of Chemistry, 2010)
In this study, the variability of soil horizons and some properties of soil such as the contents of sand, silt, clay, organic matter, bulk density, field capacity, permanent wilting point and horizontal saturated hydraulic conductivity were investigated of the soil along a left transect perpendecular to the Yesilirmak River plain by sampling five pits and one trench. The results showed that the variability of horizons was small or the horizons and their depths were similar to neighbour profiles, except for the neighbour profiles between which a main discriminating route existed. For the profiles far from the river bed, while changing for a couple of layers, in general sand contents decreased depending on depth which was vice versa for the clay content. Excluding the values for the surface layers, the bulk density values decreased depending on the distance from the river. Though it was not much strong, available water holding capacity increased depending on the distance from the river and the depth within the same profile. In general, the horizontal saturated hydraulic conductivity values decreased depending on depth within the profiles.